Legal Pluralism In The Process Of Ngadegang Bandesa Adat, Kelian Adat Or Other Names In Customary Village In Bali - I Putu Sastra Wibawa; Ida Bagus Alit Yoga Maheswara; Komang Indra Apsaridewi (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
There is regulation of State Law and Customary Law in the Ngadegang Bandesa Adat/ Kelian Village or Other Names and Prajuru Desa Adat. By theory including pluralism law in Hanging out Bandesa Adat/ Kelian Desa Adat or Other Names and Prajuru Desa Adat in Bali. How Settings and Models of Legal Pluralism in Ngadegang Bandesa Adat/ Kelian Desa Adat or Other Names and Prajuru Desa Adat Interesting For studied. This writing use method study normative law. Problem discussed with approach regulation legislation, approach analysis laws and approaches draft law. Problem studied with use source material Primary law refers to provisions regulation legislation, as well use source material law secondary, deep form bibliography, articles law as well as literacy other. Collection material law done with technique quote, next processed and analyzed with theory pluralism law, then narrated in a way descriptive, for Then concluded